A comparative analysis of macroeconomic forecasts accuracy in Spain and Romania - Mihaela Simionescu (UTMS Journal of Economics, 2015)
In this study a comparative analysis of the forecasts accuracy for Spain (developed country) and Romania (developing country) was developed for the crisis period (2009 - 2013). The providers are national forecasters: Bank of Spain and FUNCAS (Spanish Savings Banks Foundation) for Spain and two anonymous experts for Romania (E1 and E2). Only for the unemployment rate the Spanish institutes provided more accurate forecasts, for the rest of the variables (inflation rate, private consumption and GDP growth) the Romanian institutes giving more accurate predictions. However, the results are contradictory for the accuracy assessment in each country, the U1 Theil's statistic and the accuracy tests (Diebold-Mariano test and Wilcoxon's signed rank test) indicating different hierarchies. All in all, for inflation rate, unemployment rate and GDP growth in Romania, E2 provided more accurate forecasts. In Spain, FUNCAS offered better forecasts for GDP growth and private consumption during 2009 - 2013.
Keywords: E27; E37; C52; C53; 330; directional accuracy; forecasts; predictions; Diebold-Mariano test